Peer-assessment ability of trainees in clinical restorative dentistry: can it be fostered? - Ghaith Alfakhry; Khattab Mustafa; M. Abdulhadi Alagha; Obada Zayegh; Hussam Milly; Feras Al Shwikani; Issam Jamous (Nature Publishing Group, 2022)
Abstract Objectives The study was conducted to investigate whether peer-assessment among dental students at the clinical stage can be fostered and become closer to that of experienced faculty assessors. Methods A prospective pilot study was conducted in 2021 at the Faculty of Dentistry, Damascus University. Sixteen 5th year clinical students volunteered to participate in the study. A modified version of the validated Peer Direct Observation of Procedural Skills (Peer-DOPS) assessment form was used together with a grading rubric. Participants undertook peer-assessment on their colleagues across three encounters. The difference between peers and faculty assessment was the main variable. Results The mean difference between peers and faculty assessment decreased after each encounter with a significant difference and a medium effect size between the first and third encounters (p = 0.016, d = 0.67). Peer-assessment was significantly higher than faculty, however, the overestimation declined with each encounter reducing the difference between peer- and faculty assessment. Peers' perception of the educational benefit of conducting assessment was overwhelmingly positive, reporting improvements in their own performance. Conclusion This pilot study provides preliminary evidence that dental students assessment ability of their peers can be fostered and become closer to that of experienced faculty assessment with practice and assessment-specific instruction.